Diagnostic accuracy of magnetic resonance imaging in detecting depth of invasion of tongue cancers. Issue 10 (December 2021) - Mair, M.; Raj, L.; Mahmood, S.; Fagiry, R.; Ahmed, M.M.; Menon, I.; Ibrahim, N.; Ameerally, P.; Baker, A.; Vaidhyanath, R.
Abstract: The recent eighth edition of the American Joint Committee on Cancer (AJCC) staging system has introduced depth of invasion (DOI) as one of its important components. DOI is also important for deciding neck management in superficial tongue cancers. Magnetic resonance imaging (MRI) is mainly used to assess DOI, and in this study we have evaluated the efficacy of MRI to detect it. This is a retrospective study consisting of 60 treatment-naïve tongue cancer patients operated on between July 2017 and June 2019. Patients underwent MR imaging on an Optima MR450W 1.5T unit, and MRI was reported by two experienced head and neck radiologists. Postoperative histological DOI was considered the gold standard. The correlation coefficient was derived for postoperative DOI and MRI-detected DOI. A subgroup analysis of superficial tongue cancer was also done. The mean MRI DOI was 13.7 mm and the mean histological DOI 12.45 mm. The shrinkage factor was 0.6 mm. Pearson's correlation coefficient was 0.80 (p=<0.001) for Radiologist 1 and 0.85 (p=<0.001) for Radiologist 2. The interobserver variation was low, with a correlation coefficient between the two radiologists of 0.965 (p=<0.001). For superficial tongue cancers there was moderate correlation for MRI and histologically-detected DOI with a kappa value of 0.681 (p=0.03). As per the ROC curve, the cut-off value for MRI DOI to predict nodal metastasis was 4.6 mm. MRI has high reliability to predict the DOI of tongue cancers. The interobserver variation was low. The diagnostic accuracy in cases of superficial tongue cancer was moderate.